Pleurodesis for malignant pleural effusions: current controversies and variations in practices. - West, S; Davies, R; Lee, Y (2004)
PURPOSE OF REVIEW: Malignant pleural effusions are common, and pleurodesis remains the best method to control re-accumulation of the pleural fluid. There are few randomized controlled trials studying the optimal management of malignant pleural effusions. A recent international survey of pleurodesis practice has highlighted variations in how pleurodesis is performed worldwide. Future research should target these areas of variation to determine the best practice protocols. RECENT FINDINGS: The selection of pleurodesing agents remains controversial. Talc is more effective, but is associated with more adverse effects. Talc pleurodesis is followed by systemic and pulmonary inflammation. This is probably related to systemic embolization of talc following its intrapleural administration, though there are other potential causes that may also play a role. SUMMARY: The practice of pleurodesis varies considerably among individual pulmonologists and among different countries, in most technical aspects. This review serves to highlight some of these variations in practice, as well as reviewing the current literature on pleurodesis practice.